Household-level determinants of at-source waste segregation in Kathmandu Metropolitan City - Shrestha, Shyam Babu; Lamba , Nitin (A Bi-annual South Asian Journal of Research & Innovation, 2026)
Due to surging population, urbanization, and changing consumption behaviors in Kathmandu Metropolitan City, the production of solid waste in the household has become highly intensive, which imposes drastic strain on the waste management system in Kathmandu Metropolitan City. As landfills are overstretched, as municipal collection systems strive to keep up with the pace, at-source waste segregation has risen to the legitimacy of decreasing landfill dependence and improving environmental sustainability. This paper has discussed the segregation behaviour at the household-level and determined the socio-demographic, perception based, and infrastructural parameters that determine household participation. The research design employed has been a quantitative research design which is done through secondary data containing collected data on municipal records, environmental management reports, waste collection data and ward level data. The level of segregation as well as differences across wards have been measured using descriptive statistics, correlation matrices, logistic regression analysis and spatial mapping techniques. The findings have revealed that households have only practiced the three elements of proper waste management through the following percentages where 36% of the households have practiced all three parts of managing waste such as separating organic and inorganic waste, recycles of waste materials, separation of organic waste, and disposing of it at the correct time (67%). Variables based on awareness have proved to be most predictive of the right segregation behavior including exposure to media, environmental awareness, and a regular news viewer, socio-demographic variables proved weak or unimportant. The paper ends up finding that more awareness campaigns, improved access to environmental information and better municipal communication systems are needed to ensure that people in Kathmandu Metropolitan City remain consistent with at-source segregation, recycling and responsible disposal of waste.